2011
DOI: 10.1007/s10147-011-0206-6
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous multiple adenocarcinomas of the pancreas

Abstract: We report a rare case of metachronous multiple adenocarcinoma of the pancreas. A 59-year-old Japanese man visited our institute for a routine workup as a hepatitis C virus carrier, resulting in detection of a 3-cm tumor in the pancreatic body by screening echogram. Results from several imaging modalities were consistent with pancreatic carcinoma. Distal pancreatectomy along with dissection of partial gastrectomy, transverse colectomy, and lymph node dissection were performed in November 2003. Histological exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…7 Ikematsu et al reported a 59-year old man who underwent sequential distal pancreatectomy and pancreaticoduodenectomy for metachronous multiple adenocarcinomas of the pancreas. 8 For multiple tumors of the pancreas, the choice of surgery should be based on the nature of pathology and follow the principle of oncological resection. If possible, pancreatic parencyma should be preserved to reduce long-term complications and improve quality of life of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Ikematsu et al reported a 59-year old man who underwent sequential distal pancreatectomy and pancreaticoduodenectomy for metachronous multiple adenocarcinomas of the pancreas. 8 For multiple tumors of the pancreas, the choice of surgery should be based on the nature of pathology and follow the principle of oncological resection. If possible, pancreatic parencyma should be preserved to reduce long-term complications and improve quality of life of the patients.…”
Section: Discussionmentioning
confidence: 99%